Cooking with elaborate recipes can reduce the formation of mutagenic heterocyclic amines and promote co-mutagenic amines. Issue 3 (4th March 2019) - Khan, Mohammad Rizwan; Busquets, Rosa; Naushad, Mu; Puignou, Lluís
ABSTRACT: Heterocyclic amines (HCAs) are foodborne carcinogens for which their formation is highly dependent on cooking conditions. HCAs have been commonly quantified in food items prepared with simple procedures. This approach is suitable for elucidating HCAs' formation, but it only partially reflects the contamination in consumed food. In the current investigation, the generation of HCAs has been investigated in fried beef items prepared with elaborated cooking recipes, and their occurrence has been compared with control beef fried without the addition of ingredients other than oil. The food recipes that included a variety of food ingredients had lower yields of mutagenic HCAs (≥47% reduction, with individual HCA levels ranging between 0.01 and 2.22 ng/g) with respect to the control beef. In contrast, the co-mutagens norharman and harman were formed generally at greater levels (up to three times the contamination in the control fried beef) in the items prepared including a greater variety of ingredients. Graphical Abstract: